Digital broadcasting and business opportunities for Universities in Indonesia - Supadiyanto; Heri Setyawan Budi Santoso (Penerbit Universiti Kebangsaan Malaysia, 2024)
The implementation of digital broadcasting policies in Indonesia was marked by the issuance of Law Number 11/2020 concerning Job Creation, which was followed by the migration from analog to digital broadcasting (Analog Switch Off/ASO). The dynamics of digital broadcasting are caused by the tug of war-between the legislative, executive, judiciary, academics, nongovernmental organizations, and the broadcasting media industry itself. What is the policy of digital broadcasting after the implementation of Law Number 11/2020 concerning Job Creation, especially Article 60 A regarding ASO on November 2, 2022? What are the opportunities and challenges that communication-based tertiary institutions have in utilizing digital broadcasting in Indonesia? The paradigm of this research is qualitative. Data collection techniques through observations on digital broadcasting business trends, interviews, and legal studies. As a result, the digital broadcasting policy has been running quite well so far. Although implementation in each field is constrained by various problems: infrastructure, infraculture, human resources, and the extent of territory. Findings found that higher education institutions must be able to take advantage of opportunities for digital broadcasting policies as a means of disseminating information. The latest research results indicate that universities can establish digital television companies or content providers as well as a place for distributing work for college graduates.